Antibacterial and Antioxidant Activities of Triterpenoids and Cyclic 1,7-Diarylheptanoids from the Stem Bark of Myrica salicifolia: A Combined Experimental and Computational Study - Abraham Dilnesa Gashaw; Kibrom Gebreheiwot Bedane; Taye B. Demissie; Japheth O. Ombito; Estifanos Ele Yaya; Mekonnen Abebayehu Desta (Journal of Chemistry)
Myricasalicifolia A Rich (Myricaceae) is a tree growing in Central and East Africa. Traditionally, the plant is used to treat malaria, respiratory disorders, inflammations, and infections. A new compound, 3β-O-trans-caffeoylisomyricadiol (7), was isolated from MeOH : CHCl3 (2 : 1) extract of the stem bark of Myrica salicifolia along with seven known compounds, namely, myricanone (1), myricanol (2), myricanol-11-O-β-D-xylopyranoside (3), taraxerone (4), taraxerol (5), myricadiol (6), and methyl-β-D-glucopyranoside (8). This is the first report of the isolation of taraxerene-type triterpenes from this plant. The structures were determined by a comprehensive analysis of 1D/2D NMR spectroscopy, HR-MS, and by comparison with literature data. The compounds showed a wide range of DPPH scavenging activities from very weak (IC50 value = 282.61 μM) to very strong (IC50 = 13.48 μM). Antibacterial activities of the compounds were evaluated using the disk diffusion agar method, where some of the compounds showed modest antibacterial activities against S. pyogenes and S. aureus at 250 μg/mL. Compounds 2, 3, and 7 were assessed for their in silico molecular docking analysis. The lowest binding affinity for compound 7 was found to be −7.26 to −10.35 kcal/mol against PqsA protein of P. aeruginosa, pyruvate kinase (PK) enzyme of S. aureus, LuxS protein of S. pyogenes, and DNA gyrase B of E. coli, which showed better binding affinity compared to the standard drug ampicillin (−7.36 to −8.03 kcal/mol) and ciprofloxacin (−6.19 to −6.83 kcal/mol). In silico ADMET predictions revealed that compounds 3 and 8 met all the requirements for pharmacokinetic properties.